ANALISA KELAYAKAN TARIF AIR BERDASARKAN PENGEMBALIAN BIAYA PENUH DAN SENSITIVITAS NPV - Ari Sandhyavitri; Dewi Herlina (Eco Rekayasa: Jurnal Teknik Sipil, 2015)
The objectives of this research study were to : (i) investigate how much water tariffs should be paid by consumer in order to serve the project investement and operation based on the full cost recovery schemes, and (ii) investigate sensitivity factors affeted to project NPV.  This study fokus on the Dumai,water development project, Riau Province. The project investment was approximatelly Rp. 82,34 billion  (Alternative 1 for water treatment facility of 80 l/sec) and Rp. 134,308 million (Alter-native 2 for watar treatment facility of 160 l/sec) for 25 years. Based on the  economic analysis, it was revealed that; the Net Present Value (NPV) of  the alternative 1 project was Rp. 4.4 billion (with water tariffs of Rp. 7.000,-/m3 for a household and Rp 9.000,-/m3 for an industrial sector), BCR =  1,135, and IRR = 16,829 %.  This IRR value is higher then bank interst rate (12%). Alternative 2 will yield NPV of 40 billion (with tariff of Rp. 5.700,-/m3 for Household and Rp . 8.000, -/m3 for an industrial sector), BCR= 1,122 and IRR = 16,433 % . Based on these economic analysis, this project was considered feasible to proceed. The factors that are relatively sensitive for the NPV of project were; chemicals, electricity and fuel, staff salaries, and interest rates.